Kuiz semanis kelulut / Nor Azalea Mohd Azahar - Mohd Azahar, Nor Azelea (Perpustakaan Tun Abdul Razak, 2021)
Perpustakaan Tun Dr. Ismail (PTDi) telah mengadakan Pertandingan Kuiz Semanis Kelulut secara atas talian.